Shaping Selves: Negotiating Freedom and Discipline in the Alternative Education of Sanggar Kanigara - Karina Ita Apulina Bangun (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This research aims to analyse how power and knowledge operate in the context of alternative education in Indonesia, and how they affect subject formation and practices within it. It also aims to contribute to a more comprehensive understanding of how freedom of learning is implemented in the context of alternative education. During a six-month ethnographic case study at an alternative school called Kanigara (a pseudonym) located in Central Java, I engaged as a volunteer facilitator. My approach combined participant observation with in-depth interviews with facilitators and students, along with an analysis of institutional documentation. The “freedom to learn” discourse cultivates a keen sense of individual agency among students. The practical application of an ambiguous disciplinary framework that replaces the traditional rules with “agreement”, however, faces challenges in consistently cultivating communal responsibility. This flexibility results in significant behavioural inconsistencies and a complex process of identity negotiation between individual autonomy and community accountability. Furthermore, student autonomy in individualised research projects is frequently constrained by operational dependence on external factors, primarily parental schedules and resources, revealing the program’s nature as a constrained ‘heterotopia’ subject to external market logic. These dynamics reflect a critical internal tension: with a flexible structure, such models risk becoming what facilitators themselves described as a “fairy tale school” that inadequately prepares students for the competitive and rule-bound complexities of society, underscoring the need for a balance between autonomy and formal framework.